Correlation between age, working period and work-related musculoskeletal complaints with nordic body map among fishermen - Tualeka, Abdul Rohim; Jalaludin, Juliana; Salesman, Frans; Wahyu, Atjo; Daika, Nefri (Iranian Public Health Association, 2020)
Musculoskeletal Disorders (MSDs)are impair-ments of the bodily structures, such as muscles, joints, tendons, ligaments and nerves, which are caused or aggravated primarily by the perfor-mance of work in which work is carried out.The International Labor Organization (ILO) in 2013 in The Prevention of Occupational Disease pro-gram notes that 59% of musculoskeletal com-plaints represented by carpal tunnel syndrome (CTS) were the most common complaints of the overall disease records in Europe in 2005, where-as in Korea MSDs experienced a very high in-crease from 1,634 in 2001 to 5,502 in 2010(1).Statistics in 2011 show that 67 million workers in Indonesia were in the informal sector and 30% of them were fishermen(2). Fisherman also hasa risk to got MSDs because fisherman usesmuch exertion which results in excessive stretching of muscles.